Pegaruh Work-Life Balance dan Disiplin Kerja terhadap Kinerja Pegawai Dinas Perumahan dan Kawasan Pemukiman Kota Bandung - Ramadhan, Wahyu; Siddiq, Andhika Mochamad (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Managing volunteer labor is a critical and strategic process for ensuring the success of any organization that focuses on increasing volunteer labor to achieve organizational goals. This study aims to study the balance between work and life and discipline in the upkeep and repair of the Bandung city region. The method of analysis employed is a quantitative approach using descriptive verifiable. This sample is being drawn utilizing a primary random sampling method with 100 participants chosen based on Slovin's rumor. Using a scale of about five buttons, the questionnaire's measurement. The findings reveal that work-life balance and work ethic have a favorable and noteworthy effect on the output of caregivers in the Dinas Perumahan and Kawasan Pemukiman Kota Bandung simultaneously, contributing 0.443 at or 44.3%, while other variables negatively impact 55.7% of the work